2019
DOI: 10.1088/1475-7516/2019/11/034
|View full text |Cite
|
Sign up to set email alerts
|

Measuring neutrino masses with large-scale structure: Euclid forecast with controlled theoretical error

Abstract: We present a Markov-Chain Monte-Carlo (MCMC) forecast for the precision of neutrino mass and cosmological parameter measurements with a Euclidlike galaxy clustering survey. We use a complete perturbation theory model for the galaxy one-loop power spectrum and tree-level bispectrum, which includes bias, redshift space distortions, IR resummation for baryon acoustic oscillations and UV counterterms. The latter encapsulate various effects of short-scale dynamics which cannot be modeled within perturbation theory.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
171
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 148 publications
(184 citation statements)
references
References 181 publications
(437 reference statements)
12
171
1
Order By: Relevance
“…[93], which showed that the leading effect of massive neutrinos is always a suppression of the linear power spectrum, and any residual scale dependence of this suppression is insignificant even for volumes as large as 100 ðGpc=hÞ 3 . This observation was also confirmed in various forecasts, e.g., [17,96]. Given these reasons, we expect that using the usual FFTLog formulas in the presence of massive neutrinos will be a good approximation even for future surveys like DESI or Euclid.…”
Section: E Neutrino Massessupporting
confidence: 61%
See 4 more Smart Citations
“…[93], which showed that the leading effect of massive neutrinos is always a suppression of the linear power spectrum, and any residual scale dependence of this suppression is insignificant even for volumes as large as 100 ðGpc=hÞ 3 . This observation was also confirmed in various forecasts, e.g., [17,96]. Given these reasons, we expect that using the usual FFTLog formulas in the presence of massive neutrinos will be a good approximation even for future surveys like DESI or Euclid.…”
Section: E Neutrino Massessupporting
confidence: 61%
“…To that end, we interface CLASS-PT with the MCMC sampler MONTEPYTHON v3.0 [6,12]. We will analyze a full-shape likelihood built out of the publicly available BOSS data and products that can be accessed, 17 see Refs. [103,104] for more detail.…”
Section: Application To the Boss Datamentioning
confidence: 99%
See 3 more Smart Citations